Learning aid for inguinal canal anatomy - Ye, Tun; Myint, Yi Yi (2013)
Background The inguinal region is one of the most complex anatomic areas of human body even though it has been the subject of great interest to anatomists and surgeons because of its clinical importance. The aims of the study are to 1. Provide a simplification and in-depth understanding of the complex and confusing inguinal canal anatomy. 2. Incorporate time-effective method in learning. 3. Provide revision for coursework at any time and place. Method This study took place during the 2008 - 2009 academic years. The anatomical diagrams were prepared with the Microsoft word2007 and printed on three A-4 papers. The inguinal canal was constructed using ordinary scissors and glue. The efficacy of the model construction is evaluated by testing 10 questions regarding the anatomy of inguinal canal before (pre-test) and after (post-test) doing the construction. A 5-point scale questionnaire was used to elicit the students’ views on different teaching methods in our university.